Sosialisasi Pesantren Ramah Anak dalam Upaya Pencegahan Kekerasan Terhadap Perempuan dan Anak di Satuan Pesantren Se-Kabupaten Madiun - Eviningrum, Sulistya (Abdimas Indonesian Journal, 2023)
The  aim  of  carrying out  this  community  service  activity  is  to  increase  the  knowledge and  understanding  of Islamic boarding school caregivers  regarding  bullying  behavior  or violence against women and children. This community service activity is carried out by providing legal counseling at the Population Control, Family Planning and Women's Empowerment and Child Protection (P2KBP3A) Department of Madiun Regency. Bullying and violent behavior is currently very common, especially now with increasingly sophisticated technology so that violent behavior and actions can easily be accessed. Violent behavior is carried out not only by adults but also by children, in fact in recent cases there have been many cases of violent behavior being carried out by children. Socialization regarding Efforts to Prevent Violence Against Women and Children in Islamic Boarding School Units, part of how to deal with violence which is usually carried out by caregivers or fellow students, the dangerous consequences of these acts of violence and how to overcome them if they become victims, as well as educating that the state needs to protect the rights of every person. citizens through criminal sanctions for perpetrators of violence.